Conversational Code-Switching among Bilinguals in Junior High School Reunion Event - Lestari, Firnantia Lara (Humaniora, 2018)
The goal of this research was to find out the types of code-switching, and the reason of the participants performs code-switching in the conversation. Research used a qualitative approach. The result shows that three types of code-switching occurs in the conversation among bilingual in the junior high school reunion, they are intra-sentential mixing, intra-lexical code mixing, involving a change of pronunciation. The functions of codeswitching usage are as the marker of changing topic, to show their closeness as an old friend, and to show the close relationship among others. The close relationship between the speakers makes the feel free to switch from one language to another. Furthermore, the switching code also has another function as repetition is used to clarify the utterances of by the speakers. Moreover, the code-switching in the conversation are able to declare the excitement feeling towards a particular topic (the interesting topic) that they are talking about.